Hybrid Identification System with ARX and Fast Fourier Transform in Application of a Quarter of Vehicle Half Active Suspension - M, Noveri Lysbetti; R., Antonius (Makara Journal of Technology, 2006)
Hybrid Identification System with ARX and Fast Fourier Transform in Application of a Quarter of Vehicle Half Active Suspension. In a control system problem, identification system mechanism is a absolute thing, especially in adaptation controlling to disturbance changing. For that case, is needed an identification method which can identify the changing of disturbance in that system. The aim of this research is to give an alternative in system/plant identification which is a combination (hybrid) of ARX and Fast Fourier Transform. So, it is needed an algorithm design for identification process. In this case, the designed algorithm will be implemented in software that works based on Matlab. The result of car mass 500Kg in seventh second with first way disturbance is the biggest frequency at this time. Operation frequency produced is 27.4889Hz, estimation model magnitude is 1.3431E-006 and estimation model phase is -86.8307. The result of car mass 1000Kg in 15th-second, with second way disturbance is the biggest frequency at this time. Operation frequency produced is 3.9270Hz, estimation model magnitude is 1.1780E-006 and estimation model phase is 131,5950. These results show that as lighter car mass when disturbance happened by road surface, as bigger the operation frequency happen.